If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6k + -6(k + 10) = 4k + 7 Reorder the terms: 6k + -6(10 + k) = 4k + 7 6k + (10 * -6 + k * -6) = 4k + 7 6k + (-60 + -6k) = 4k + 7 Reorder the terms: -60 + 6k + -6k = 4k + 7 Combine like terms: 6k + -6k = 0 -60 + 0 = 4k + 7 -60 = 4k + 7 Reorder the terms: -60 = 7 + 4k Solving -60 = 7 + 4k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-4k' to each side of the equation. -60 + -4k = 7 + 4k + -4k Combine like terms: 4k + -4k = 0 -60 + -4k = 7 + 0 -60 + -4k = 7 Add '60' to each side of the equation. -60 + 60 + -4k = 7 + 60 Combine like terms: -60 + 60 = 0 0 + -4k = 7 + 60 -4k = 7 + 60 Combine like terms: 7 + 60 = 67 -4k = 67 Divide each side by '-4'. k = -16.75 Simplifying k = -16.75
| x*x+5x=11 | | 0.6x-22.9=1.5x-18.4 | | 18x^2-15x-12=0 | | -5-6=4x+7-3x | | /5-6=4x+7-3x | | =-3(4x+2)+5(2x-3) | | 200=x+35 | | 256-2x^2=0 | | 24-12h=4(5-3h) | | 1/2(4-8x)=1/3(4x+7)-3 | | x^2+128=0 | | -(2x-7)-2x=27 | | =-10x+4(3x-2)+15 | | 3(x-2)=39-2x | | 2*y^2-3*y=0 | | 5(g-7)+2(g-5)=0 | | =12+2(3b+4)-9b | | 4=8x+3 | | 2x/3+x/3=3/4+x/2 | | 4-11=z/6 | | -6=3p+3(3p+3) | | =-n-5(-6-7n) | | 2x+8=5x-7 | | 3(1x-5)/2=2(1x+5)/3 | | 3(z+8)=z | | x+295=11x-5 | | =8(2-3x)+8x | | 3x+4-4x-10= | | 6a-4=8a+2 | | 26=3x-1 | | z/7=5-18 | | 5(y+1)+y=6y+5 |